2001
DOI: 10.1080/110381201300173621
|View full text |Cite
|
Sign up to set email alerts
|

The Experience and Management of Temporality in Five Cases of Dementia

Abstract: Nyga Ê rd L, Johansson M. The experience and management of temporality in ×e cases of dementia. Scand J Occup Ther 2001; 8: 85-95. How persons with dementia may experience time, temporal problems and temporal adaptations in their everyday lives is explored. The clinical implementation process and outcome of time aid interventions in ve cases are also described. Data were collected through initial interviews with ve participants, diagnosed with dementia, and with three spouses. Thereafter, time aids were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 9 publications
4
31
2
Order By: Relevance
“…Therefore, we also wanted to uncover the strategies that were practised by the persons with dementia themselves. In former studies of adaptational and compensational efforts among persons with dementia, a variety of both spontaneous and planned strategies for managing problems in everyday life have been discovered (24, 26–30). Consequently, we expected such responsive efforts (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we also wanted to uncover the strategies that were practised by the persons with dementia themselves. In former studies of adaptational and compensational efforts among persons with dementia, a variety of both spontaneous and planned strategies for managing problems in everyday life have been discovered (24, 26–30). Consequently, we expected such responsive efforts (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In a familiar setting, they found initiation easier and often habitual. Nygard and Johansson (2001), in their study of temporality among those with dementia, reported that participants relied upon their spouses to organize their day. In many cases this could be due to a change in routine or setting.…”
Section: Discussionmentioning
confidence: 99%
“…These studies are congruent with our finding that caregivers served to initiate performance of many occupations by the participant. Nygard and Johansson (2001), in their study of temporality among those with dementia, reported that participants relied upon their spouses to organize their day. Again, this is congruent with our finding that participants relied upon caregivers for initiation of occupation.…”
Section: Discussionmentioning
confidence: 99%